Distributed platforms proceedings of the IFIP/IEEE International Conference on Distributed Platforms: client/server and beyond: DCE, CORBA, ODP and advanced distributed applications - Schill, Alexander (Chapman & Hall, 1996)
Presents the research worldwide on distributed computing platforms. This title presents the proceedings of the IFIP/IEEE International Conference on Distributed Platforms held in Dresden, Germany in February 1996.